Panorama of Prevalence of Malocclusion, Treatment Needs, Specific Occlusal Traits & Gender Distribution in Patients Seeking Orthodontic Treatment in Kolhapur Population - A Prospective Cross-sectional Study - Shraddha Subhash Shetti; Kishor Adinath Chougule (Wolters Kluwer Medknow Publications, 2013)
Aim: To assess the prevalence of malocclusion, treatment needs and specific occlusal traits among Kolhapur population. Materials & Method: The sample comprised 500 individuals: that is, 250 boys & 250 girls between the age group of 13 -20 years. The sample was drawn from among the patients reporting for the treatment of malocclusion to the department. After intraoral examination, dental casts of the patients were assessed later and scored. A mouth mirror, a ruler & a sliding digital caliper was used. For every individual, variables related to malocclusion were recorded on a specially designed registration chart. A set of 10 photographs showing a range of dental attractiveness of the aesthetic component based on IOTN was followed and the data was subjected to statistical analysis. Results: About 48.80 % individuals had Angle's Class I malocclusion; 34.60 % had Class II division 1; 2% had Class IT division 2 and 1.80% had Class Ill malocclusion. Deep-bite type of vertical malocclusion was present in 62.60% of the sample and 37.40% subjects had a normal overbite. The next most prevalent type of malocclusion was deviation of dental midlines which was found in 50.40% of sample. Orthodontic treatment need as assessed by the DHC of the IOTN were such that 24.20 %and 53.40% fell into grade 4 and grade 5 respectively. Therefore definitely requiring treatment and as assessed by the AC of the IOTN 27.40% and 18.20% sample fell into grades 8 - 10 and grade 10 respectively, as it was the least aesthetic arrangement of the dentition therefore definitely requiring treatment. Conclusions: Orthodontic treatment indices such as IOTN can be used effectively with less subjective bias to determine the orthodontic treatment need. The study suggests that there is a borderline to definite need for treatment in a large amount of population in the semirural western Maharashtra.